The efficacy and safety of different systemic combination therapies on advanced hepatocellular carcinoma: a systematic review and meta-analysis - Li, Ping; Hu, Ming; Liu, Mei; Ren, Xiangyu; Liu, Donghong; Liu, Jiluo; Yin, Jianhua; Tan, Xiaojie; Cao, Guangwen (Frontiers in Oncology, 2023)
Background and aims Systemic combinations have recently brought significant therapeutic benefits for advanced hepatocellular carcinoma (aHCC). To design the most effective combination regimens, a systematic review (PROSPERO ID: CRD42022321949) was conducted to evaluate the efficacy and safety of systemic combinations on aHCC. Methods We retrieved all the studies from PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), and China National Knowledge Infrastructure (CNKI) using the Medical Subject Headings (MeSH) terms until December 21, 2022. The effect indicators (hazard ratio [HR], relative risk [RR], and median) were pooled by a fixed- or random-effects model. A subgroup analysis was conducted according to types and specific therapies. Results In total, 88 eligible studies were selected from 7249 potential records. Each kind of combination treatment (chemotherapy plus chemotherapy, targeted plus immune checkpoint inhibitor (ICI) therapy, targeted plus chemotherapy, and targeted plus targeted therapy) had a better objective response rate (ORR) in patients with aHCC, compared to the monotherapy mostly with sorafenib (RR: 1.57 [1.44–1.71]; I2 = 30%). Of those, targeted plus ICI therapy showed better therapeutic efficiency in overall survival (median: 15.02 [12.67–17.38]), progression-free survival (median: 7.08 [6.42–7.74]), and ORR (RR: 1.81 [1.55–2.13]), compared to the monotherapy. Specifically, Atezo plus Beva showed all those benefits. Our pooled result showed all the combinations had increased ≥3 Grade treatment-related adverse events (TrAEs), with an RR of 1.25 [95% CI: 1.15–1.36], compared to the monotherapy. Conclusion The systemic combinations, especially targeted plus ICI therapy, including Atezo plus Beva, significantly improve clinical outcomes but increase side effects in patients with aHCC. Future trials should concentrate on improvement in therapeutic efficiency and reduction of toxicity of targeted plus ICI therapy. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42022321949.